Stimulating effects of submerged plants on removing of N from the water in the Daihai lake of inner Mongolia autonomous region, China - Yao, Yipeng; Jiang, Yuhan; Liu, Yuhong; Meng, Shuang; Hu, Bintao; Chen, Yixue (Frontiers in Environmental Science, 2023)
Daihai Lake, the third largest lake in Inner Mongolia Autonomous Region, is the cornerstone to maintain the ecosystem balance in this region. In recent years, due to the impacts of human activities, Daihai Lake is facing problems including size shrinking, water quality declining and biodiversity decreasing largely. Nitrogen is one of the important indicators related to the eutrophication of lakes, whereas Submerged plant can effectively purify the eutrophication substance in water bodies. Therefore, in this study, a model was established to simulate the processes of the Submerged plant absorbing the nitrogen from the water and sediment of the lake. The results showed that based on the 2019 submerged plant growth area in the Daihai Lake, the nitrogen uptake by submerged plants in the Daihai Lake in a year is 5.13t (excepe the nitrogen from dead plants decomposing and reentering the water), accounting for 4.8% of all exogenous pollution (107.895t), Moreover, our model also predicted how the changes in the scale of Submerged plant in Daihai Lake impact its nitrogen amount change over the ecological restoration process. The results showed that the submerged plants after recovery could purify 107.892t of nitrogen pollution load in 12 years, which can provide reasonable guidance for Submerged plant recovery in Daihai Lake.